2011
DOI: 10.1536/ihj.52.12
|View full text |Cite
|
Sign up to set email alerts
|

Possible Role of Damaged Neoendothelial Cells in the Genesis of Coronary Stent Thrombus in Chronic Phase

Abstract: SummaryThe mechanism(s) underlying formation of coronary stent thrombus (ST) in chronic phase is yet unclear. Endothelial cells are highly antithrombotic, therefore, it is conceivable that neoendothelial cells (NECs) covering stent struts are damaged and cause ST. This study was performed to examine the role of damaged NECs covering coronary stent struts in the genesis of occlusive or nonocclusive ST in chronic phase.(1) Forty-four patients with acute coronary syndrome (17 females and 27 males) underwent dye-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The endothelium tries to repair itself and, in the process, can cover the stent struts [46]. As the new endothelial cells may be damaged, this can lead to the formation of stent thrombi [47]. Once the endothelium is damaged, the aforementioned chain of events leading to restenosis can be activated.…”
Section: Importance Of Tribology On Stentsmentioning
confidence: 99%
“…The endothelium tries to repair itself and, in the process, can cover the stent struts [46]. As the new endothelial cells may be damaged, this can lead to the formation of stent thrombi [47]. Once the endothelium is damaged, the aforementioned chain of events leading to restenosis can be activated.…”
Section: Importance Of Tribology On Stentsmentioning
confidence: 99%
“…In animals, late stent thrombosis occurs when the neointimal thickness is within 100 μm. Neo-ECs may be damaged by friction between them and the stent struts, because of a thin interposed neointima, which should act as a cushion, resulting in late stent thrombosis [15, 16]. These findings suggest the necessity of an appropriate thickness of neointima for prevention of late stent thrombosis.…”
Section: Dye-staining Coronary Asmentioning
confidence: 99%
“…LST was observed in grade 0 or 1 group in patients with DES or BMS [10,26,50]. At 6 months after stenting, neoendothelial cells were stained in blue with Evans blue dye which selectively stains damaged endothelial cells when the neointima thickness grade was 0-1 [50,51] (Fig. 11).…”
Section: Possible Mechanisms Of Late-stent Thrombosis and Appropriate Neointimal Thickening To Prevent Restenosis And Neoendothelial Cellmentioning
confidence: 99%
“…11). In animals, the struts were visible (grade 0 or 1) when the neointimal thickness was around 88 m and LST was frequently observed when the intimal thickness was within 100 m [51]. All these findings indicated that neoendothelial cells were damaged and LST formed on the Determining exactly how to terminate this ''vicious cycle'' is an essential requisite for effective prophylactic treatment of LST.…”
Section: Possible Mechanisms Of Late-stent Thrombosis and Appropriate Neointimal Thickening To Prevent Restenosis And Neoendothelial Cellmentioning
confidence: 99%